Efficiency Evaluation of Energy Systems - Kanoğlu, Mehmet; Çengel, Yunus A.; DinCer, Ibrahim (SpringerBriefs in Energy,, 2012)
Efficiency is one of the most frequently used terms in thermodynamics, and it indicates how well an energy conversion or process is accomplished. Efficiency is also one of the most frequently misused terms in thermodynamics and is often a source of misunderstanding. This is because efficiency is often used without being properly defined first. This book intends to provide a comprehensive evaluation of various efficiencies used for energy transfer and conversion systems including steady-flow energy devices (turbines, compressors, pumps, nozzles, heat exchangers, etc.), various power plants, cogeneration plants, and refrigeration systems. The book will cover first-law (energy based) and second-law (exergy based) efficiencies and provide a comprehensive understanding of their implications. It will help minimize the widespread misuse of efficiencies among students and researchers in energy field by using an intuitive and unified approach for defining efficiencies. The book will be particularly useful for a clear understanding of second law (exergy) efficiencies for various systems. It may serve as a reference book to the researchers in energy field. The definitions and concepts developed in the book will be explained through illustrative examples.